Association of childhood and adolescence obesity with incidence and mortality of adulthood cancers. A systematic review and meta-analysis - Mohammadian Khonsari, Nami; Shahrestanaki, Ehsan; Ehsani, Amir; Asadi, Sara; Sokoty, Leily; Mohammadpoor Nami, Sahar; Hakak-Zargar, Benyamin; Qorbani, Mostafa (Frontiers in Endocrinology, 2023)
Background Prevalence and subsequent conditions of childhood and adolescent obesity are increasing. It has been seen that obesity in youth is associated with adulthood cancer. This systematic review and meta-analysis aimed to determine the pooled association of childhood obesity with cancers in adulthood. Methods In this systematic review, international electronic databases such as Scopus, PubMed, Web of Science, and EMBASE were searched using relevant keywords until February 2022. All Cohort studies assessing the association of childhood and adolescent obesity (under 18 years old) with the incidence and mortality of all types of cancers were included. Two independent reviewers screened and carried out the quality assessment of included studies. Between-studies heterogeneity was assessed using the I squared and Cochran’s Q tests. Random/fixed-effect meta-analyses were used to pool the appropriate effect sizes (Hazard ratios (HR)). Results Overall, 46 studies were found to be relevant and were included in this study. Based on the random-effects model meta-analysis, childhood obesity increased the hazard of cancer incidence and mortality in adulthood by 33% (HR: 1.33, 95%CI (1.25, 1.41)) and by 28% (HR: 1.28, 95%CI (1.13, 1.42)), respectively. In the subgroups meta-analysis, the HR of childhood obesity and adulthood cancer incidence mortality in women was higher than in men (HR=1.39, 95%CI (1.25, 1.53) vs HR= 1.20, 95%CI (1.07, 1.32)) and (HR= 1.40, 95%CI (1.10, 1.69) vs HR=1.20, 95%CI (1.04, 1.36)) respectively. Conclusion This study found that obesity in childhood and adolescence is associated with a significant increase in the incidence and mortality of cancers in adulthood. Prevention of childhood obesity, in addition to its short-term beneficial effects, can reduce the burden of cancer in adulthood